2000
DOI: 10.1101/lm.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

God's Organism? The Chick as a Model System for Memory Studies

Abstract: The young chick is a powerful model system in which to study the biochemical and morphological processes underlying memory formation. Training chicks on a one trial passive avoidance task results in a molecular cascade in a specific brain region, the intermediate medial hyperstriatum ventrale. This cascade is initiated by glutamate release and engages a series of synaptic transients including increased calcium flux, up-regulation of NMDA-glutamate receptors, membrane protein phosphorylations, and the retrograd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(151 citation statements)
references
References 98 publications
5
137
0
6
Order By: Relevance
“…Training of day-old chicks on a one-trial passive avoidance task has been reported to result in a cascade of cellular events, from immediate early gene expression, through biochemical to pharmacological changes in specific brain regions, notably the intermediate medial mesopallium (IMM; Rose and Csillag, 1985;Rose and Stewart, 1999;Rose, 2000) formerly known as the IMHV (Reiner et al, 2004). We have also found this multimodal brain region to be important in the formation of memory in both passive avoidance and bead discrimination learning paradigms (Gibbs and Ng, 1977;Gibbs and Summers, 2002a).…”
Section: Introductionmentioning
confidence: 89%
“…Training of day-old chicks on a one-trial passive avoidance task has been reported to result in a cascade of cellular events, from immediate early gene expression, through biochemical to pharmacological changes in specific brain regions, notably the intermediate medial mesopallium (IMM; Rose and Csillag, 1985;Rose and Stewart, 1999;Rose, 2000) formerly known as the IMHV (Reiner et al, 2004). We have also found this multimodal brain region to be important in the formation of memory in both passive avoidance and bead discrimination learning paradigms (Gibbs and Ng, 1977;Gibbs and Summers, 2002a).…”
Section: Introductionmentioning
confidence: 89%
“…Since the pioneering work of Grecksch and Matthies (1980), more recent data confirmed that memory consolidation might rely on two protein-synthesis-dependent phases (Freeman et al 1995;Rose 2000;Igaz et al 2002). In fear conditioning, this biphasic activation is a dynamic process as the development of one or two waves of protein synthesis is dependent on the level of training (Bourtchouladze et al 1998).…”
mentioning
confidence: 95%
“…The chick can be tested following deprivation of certain sensory stimulation without incurring the problem of having an unnatural or inadequate development that would impede any reliable experimental inference. It is not by chance that it has been dubbed by Steven Rose "the God's organism" for studies about the neurobiology of learning and memory (Rose, 2000). Furthermore, considering that several studies have been carried out on the chick's ability to reorient in the first two weeks of life (review in Vallortigara, 2009a), this species may become a particularly well-suited model for investigating the "innateness" of cognitive functions, and in this specific case, the innateness of metric sense.…”
Section: Geometrymentioning
confidence: 99%
“…The domestic chick has been a very successful animal model system in neurobiology and in the study of early learning, particularly for studies on memory consolidation, brain asymmetries, and the neural bases of memory (Andrew, 1991;Rogers, 1996;Rogers & Andrew, 2002;Horn, 2004;Matsushima et al, 2003;Rose, 2000;Vallortigara, 2000;2006a). In addition, we believe it may prove to be an excellent model to adopt in order to tackle some classical issues in developmental psychology, offering a novel battle-ground for the empirical investigation of nature-nurture issues on the origins of knowledge.…”
Section: Introductionmentioning
confidence: 99%